EFEKTIFITAS METODE KONVENSIONAL DAN EXPLICIT INSTRUCTION TERHADAP PENGETAHUAN BASIC LIFE SUPPORT PADA ANGGOTA PMR - Novia Faizatiwahida; Suratmi Suratmi; Heny Ekawati (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2022)
Basic Life Support (BLS) is an action to save lives when cardiac arrest occurs. Cardiac arrest is the number one cause of death in the world. In Indonesia BLS knowledge is still lacking. This study aims to determine the differences in the effectiveness of conventional methods and explicit instruction on the knowledge of Basic Life Support for Youth Red Cross members at SMAN 1 Ngimbang. Using pre-experimental methods (two group pre-test and post-test design). The sampling technique uses simple random sampling with 80 respondents, which are divided into intervention and control groups. Data collection using questionnaire sheets. The results of data collection were tested using the Wilcoxon Test and the Mann Whitney Test with the SPSS Version 16 program. There was an increase in knowledge after being given the conventional method with a knowledge base of 81.62 and an increase in knowledge after being given the explicit instruction method with a mean of 88 knowledge. Significant differences between conventional methods and explicit instruction on knowledge of basic life support with a p value (0.002 <0.05). Conventional and Explicit Instruction Methods can increase the knowledge of adolescent red cross members about basic life support.